Analysis of Human Behavior in the Social Environment - Duyte, Mergo (Journal Social Civilecial, 2023)
This article discusses groups, which is a broad concept that is not only related to humans, but also to living things other than humans. Group formation begins with the same feelings or perceptions in fulfilling needs. The purpose of this article is to know and understand about groups and how a general description of groups starts from understanding, the process of formation, their characteristics, types, and other things related to knowing and understanding formal groups and the behavior of individuals in therein.